Distinct Functional Domains of Nibrin Mediate Mre11 Binding, Focus Formation, and Nuclear Localization - Desai-Mehta, Ami (American Society for Microbiology, 2001)
The inherited chromosomal instability disorder Nijmegen breakage syndrome (NBS) results from truncating mutations in the NBS1 gene, which encodes the protein nibrin. Nibrin is part of a nuclear multiprotein complex that also contains the DNA repair proteins Mre11 and Rad50. Upon irradiation, this complex redistributes within the nucleus, forming distinct foci that have been implicated as sites of DNA repair. In NBS cells, nibrin is absent and Mre11 and Rad50 are cytoplasmic. In this study, the interacting domains on nibrin and Mre11 were mapped using the yeast two-hybrid system and expression of epitope-tagged constructs in NBS fibroblasts. Deletion of the carboxy-terminal 101 amino acids of nibrin eliminated its ability to interact with Mre11 and to complement the radiation sensitivity of NBS cells. However, this truncated form of nibrin could localize to the nucleus and form radiation-inducible foci. Expression of a carboxy-terminal 354-amino-acid fragment of nibrin was sufficient to direct the nuclear localization of nibrin, as well as that of Mre11 and Rad50. Despite providing some partial complementation of the radiation-sensitive phenotype, the nibrin-Mre11-Rad50 complexes in these cells were unable to form foci. These results indicate that nibrin directs not only the nuclear localization of the nibrin-Mre11-Rad50 complexes but also radiation-induced focus formation. However, direct interaction between nibrin and Mre11 is required for normal cellular survival postirradiation. Distinct domains of nibrin are required for each of these functions, focus formation, nuclear localization, and Mre11 interaction.